Morphometric Investigations of Tapi Micro Watershed, Asirgarh, Burhanpur District, MP, India with Emphasis on Geographical Data Analysis - Mayura Deshmukh; S. F. R. Khadri (New Visions in Science and Technology Vol. 7, 2021)
Morphometry is a significant pointer to recognize the morphological and hydrological characteristics of earth. Current investigation intentions to identify the morphological characteristics of Tapi micro watershed. In the field of current day geographical and geological studies, geospatial investigation is, remote sensing (RS), geographical information system (GIS) and global positioning system (GPS) have showed to be a successful device. Geographical information system and Remote sensing techniques have been implemented for the identification of different morphological features and to evaluate their presence in a hilly river basin of Asirgarh volcanic, which is located in the Burhanpur district, MP, India. Morphometric analysis is a quantitative description and analysis of landforms. Morphometry of any drainage basin is a systematic method has a great importance in understanding hydrological behaviour of the basin. The morphometric parameters of the study area have been discussed with respect to three types of aspects such as linear, areal and relief aspects. The morphometric parameters of study area were measured are stream order, stream length, bifurcation ratio, drainage density, drainage frequency, drainage texture, form factor, circulatory ratio, elongation ratio and compactness ratio, etc. The results of morphometry undoubtedly specify relations midst numerous morphometric attributes of the basin and help to recognize their role for delineating groundwater potential zones for the sustainable development of the region. Various maps have been prepared using remote sensing and GIS techniques to delineate groundwater potential zones for the sustainable development of the Tapi micro watershed. The drainage network in the study area is dendritic to sub-dendritic, indicating that lithology and terrain have an impact on drainage pattern.